2018
DOI: 10.1371/journal.pone.0193371
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of microRNAs in the intestinal tissues of sheep (Ovis aries)

Abstract: Sheep are small ruminants, and their long intestines exhibit high digestive and absorptive capacity in many different rearing conditions; however, the genetic bases of this characteristic remains unclear. MicroRNAs (miRNAs) play a major role in maintaining both intestinal morphological structure as well as in regulating the physiological functions of this organ. However, no study has reported on the miRNA expression profile in the intestinal tissues of sheep. Here, we analyzed and identified the miRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…Based on a search in the miRBase database, and in BLAST with other species, the DE miRNAs were found to be conserved between Homo sapiens (has-miR, chromosome 21) and Bos taurus (bta-miR, chromosome 14). Intriguingly, most of the identified DE miRNAs were located on chromosome 18 in sheep, which corroborates findings of others who have reported the highest density of miRNA on ovine chromosome 18 (2.40 miRNA loci per Mbp with a total 174 miRNA loci) based on miRNAome analysis of ovine heart, intestine, and muscle tissues [48][49][50]. Collectively, these results highlight the importance of ovine chromosome 18 in terms of unravelling the regulation of ovine innate immune response.…”
Section: Discussionsupporting
confidence: 89%
“…Based on a search in the miRBase database, and in BLAST with other species, the DE miRNAs were found to be conserved between Homo sapiens (has-miR, chromosome 21) and Bos taurus (bta-miR, chromosome 14). Intriguingly, most of the identified DE miRNAs were located on chromosome 18 in sheep, which corroborates findings of others who have reported the highest density of miRNA on ovine chromosome 18 (2.40 miRNA loci per Mbp with a total 174 miRNA loci) based on miRNAome analysis of ovine heart, intestine, and muscle tissues [48][49][50]. Collectively, these results highlight the importance of ovine chromosome 18 in terms of unravelling the regulation of ovine innate immune response.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the miRNAs that we identified were mostly distributed in the 20-24 nt length range, with the greatest abundance of 22 nt miRNAs (Fig 1D and 1E). This finding is consistent with the typical length distribution of miRNAs found in most mammals, for example, sheep [37], pig [38], and mouse [39]. A statistical analysis of the identified miRNAs in various species revealed that 534 miRNAs were annotated in and related to humans, 489 miRNAs were related to cattle, and 263 miRNAs were related to goats, with fewer miRNAs annotated to goats than to humans and cattle ( Fig 1F).…”
Section: Discussionsupporting
confidence: 87%
“…The primer sequence of oar-miR-199a-3p, oar-let-7c, oar-let-7i, and oar-miR-143 referred to Jin et al [20]. The primer sequence of oar-miR-200b and oar-miR-10a referred to Hou et al [21]. The primer sequence of oar-miR-103 referred to Wu et al [22].…”
Section: Polymerase Chain Reaction (Pcr) Verificationmentioning
confidence: 99%